71 Prediction of response to rituximab in SLE using a validated two-score system for interferon status. (April 2019) - Alase, Adewonuola; Wigston, Zoe; Burska, Agata; Hensor, Elizabeth; Psarras, Antonios; Md Yusof, Md Yuzaiful; Reynolds, John; ,; Wittmann, Miriam; Bruce, Ian N; Vital, Edward
Abstract : Background: Rituximab is used for resistant SLE but clinical response varies. Although biomarkers of time to relapse have been validated, there are few biomarkers to predict initial response. Interferon status may predict response to rituximab and anti-TNF in RA. We previously validated two interferon-stimulated gene expression scores (IFN-Score-A and IFN-Score-B) that improved prediction of clinical outcomes in SLE. IFN-Score-A included most commonly reported ISGs and predicted flares and glucocorticoid requirements. IFN-Score-B included ISGs that respond to multiple IFN subtypes and predicted development of SLE in At-Risk individuals. Diagnosis of SLE was associated with both scores, while only IFN-Score-B was elevated in RA. The British Society for Rheumatology Biologics Registry (BILAG-BR) collects data and samples for rituximab-treated patients in the UK. MASTERPLANS is an MRC-funded consortium to identify predictors of response. Methods: This is a preliminary analysis of the first rituximab-treated patients in the BILAG-BR with complete data. Patients were recruited if they were starting a first cycle of rituximab for active SLE (BILAG A or 2xBILAG B) despite previous cyclophosphamide or mycophenolate mofetil. Disease activity was measured using BILAG-2004. Clinical response was defined as improvement by ≥1 grade in active BILAG-2004 systems with no worsening in other systems. Whole blood was collected into TEMPUS tubes and RNA extracted. IFN-Scores were measured using a custom Taqman array as previously described, normalised to PP1A [El Sherbiny et al. Sci Rep 2018]. Multivariate logistic regression was used to test IFN-Scores and baseline clinical covariates as predictors of BILAG response at 6 months. Results: Samples were available from 147 patients, of whom 84 had complete baseline and 6 month clinical data available and were included in this analysis. 40/84 (47.6%) patients had BILAG response at 6 months. In univariate and multivariate analysis, high IFN-Score-B expression was significantly associated with clinical response (see table 1 ). Conclusions: This preliminary analysis suggests that assessment of IFN activity has a role in prediction of response to rituximab. A novel IFN score (Score B) was more predictive than classic ISGs (Score A). These results add to a body of work showing that IFN-Score-B predicts clinically significant outcomes independently of overall IFN activity. Future work will analyse this biomarker in a larger cohort of patients and integrate with other putative clinical and biological predictors of response. Funding Source(s): Medical Research Council, National Institute of Health Research